Larvicidal, antimicrobial and brine shrimp activities of extracts from Cissampelos mucronata and Tephrosia villosa from coast region, Tanzania - Erasto Paul; Mihale Matobola J; Kidukuli Abdul W; Innocent Ester M; Mbwambo Zakaria H; O Nondo Ramadhani S; Moshi Mainen J (BMC, 2011)
Abstract Background The leaves and roots of Cissampelos mucronata A. Rich (Menispermaceae) are widely used in the tropics and subtropics to manage various ailments such as gastro-intestinal complaints, menstrual problems, venereal diseases and malaria. In the Coast region, Tanzania, roots are used to treat wounds due to extraction of jigger. Leaves of Tephrosia villosa (L) Pers (Leguminosae) are reported to be used in the treatment of diabetes mellitus in India. In this study, extracts from the roots and aerial parts of C. mucronata and extracts from leaves, fruits, twigs and roots of T. villosa were evaluated for larvicidal activity, brine shrimps toxicity and antimicrobial activity. Methods Powdered materials from C. mucronata were extracted sequentially by dichloromethane followed by ethanol while materials from T.villosa were extracted by ethanol only. The extracts obtained were evaluated for larvicidal activity using Culex quinquefasciatus Say larvae, cytotoxicity using brine shrimp larvae and antimicrobial activity using bacteria and fungi. Results Extracts from aerial parts of C. Mucronata exhibited antibacterial activity against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Vibrio cholera, Bacillus anthracis, Streptococcus faecalis and antifungal activity against Candida albicans and Cryptococcus neoformans. They exhibited very low toxicity to brine shrimps and had no larvicidal activity. The root extracts exhibited good larvicidal activity but weak antimicrobial activity. The root dichloromethane extracts from C. mucronata was found to be more toxic with an LC50 value of 59.608 μg/mL while ethanolic extracts from root were not toxic with LC50>100 μg/mL). Ethanol extracts from fruits and roots of T. villosa were found to be very toxic with LC50 values of 9.690 μg/mL and 4.511 μg/mL, respectively, while, ethanol extracts from leaves and twigs of T. villosa were found to be non toxic (LC50>100 μg/mL). Conclusion These results support the use of C. mucronata in traditional medicine for treatment of wounds. Extracts of C. mucronata have potential to yield active antimicrobial and larvicidal compounds. The high brine shrimp toxicity of T. villosa corroborates with literature reports that the plant is toxic to both livestock and fish. The results further suggest that T. villosa extracts have potential to yield larvicidal and possibly cytotoxic compounds. Further studies to investigate the bioactive compounds responsible for the observed biological effects are suggested.